2021
DOI: 10.1186/s12302-021-00546-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate consumption by the oxidation of sulfides during an enhanced natural attenuation project at a contaminated site in Berlin, Germany

Abstract: Background Organic pollutants at contaminated sites are often eliminated naturally by biological degradation. The redox processes responsible can be enhanced by infiltrating electron acceptors such as nitrate or sulfate into the aquifer. However, the addition of oxidative agents can lead to undesired side-effects in the saturated soil zone such as the consumption of nitrate by the oxidation of sulfides contained in the aquifer. Laboratory-scale 1D column experiments in up flow mode were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Interestingly, as shown in Figure 4 c, some undesirable peaks appeared at 162.97 and 167.85 eV, indicating a S–S bond [ 23 ] and sulfate salt (SO 4 2− ) state [ 24 ], in S 2p of the CuCrS 2 core, respectively. The SO 4 2− salt peaks might be attributed to the oxidizing activity of nitrate salts in Cr(NO 3 ) 3 with DDT, as a sulfur source, which probably results in the formation of SO 4 2− in the CuCrS 2 core level [ 25 ]. As proof, when the ZnS shell was coated, undesired peaks did not appear in the S 2p survey, which indicated that no other states were formed when nitrate salt was not present in the ZnS shell coating.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, as shown in Figure 4 c, some undesirable peaks appeared at 162.97 and 167.85 eV, indicating a S–S bond [ 23 ] and sulfate salt (SO 4 2− ) state [ 24 ], in S 2p of the CuCrS 2 core, respectively. The SO 4 2− salt peaks might be attributed to the oxidizing activity of nitrate salts in Cr(NO 3 ) 3 with DDT, as a sulfur source, which probably results in the formation of SO 4 2− in the CuCrS 2 core level [ 25 ]. As proof, when the ZnS shell was coated, undesired peaks did not appear in the S 2p survey, which indicated that no other states were formed when nitrate salt was not present in the ZnS shell coating.…”
Section: Resultsmentioning
confidence: 99%